Capital market imperfections and the theory of optimum currency areas - Pierre-Richard Agénor; Joshua Aizenman (University of California, Economics Department, 2008)
This paper studies how capital market imperfections affect the welfare effects of forming a currency union. The analysis considers a bank-only world where intermediaries compete in Cournot fashion and monitoring and state verification are costly. The first part determines the credit market equilibrium and the optimal number of banks, prior to joining the union. The second part discusses the benefits from joining a currency union. A competition effect is identified and related to the added monitoring costs that banks may incur when operating outside their home country, through an argument akin to the Brander- Krugman 'reciprocal dumping' model of bilateral trade. Whether joining a union raises welfare of the home country is shown to depend on the relative strength of 'investment creation' and 'intermediation diversion' effects.
Keywords: E43; F36; G28; 330; Finanzmarkt; Unvollkommener Markt; Währungsunion; Optimaler Währungsraum; Wohlfahrtsanalyse; Theorie